Emotional intelligence and job satisfaction among staff nurses: a cross-sectional study - Sharma, Dinesh Kumar; Dangi, Prakash; Sharma, Maneesh Kumar; Patidar, Jayesh; Kumar, Tarun; Vats, Meena (International Journal of Research in Medical Sciences, 2023)
Background: Emotional intelligence and job satisfaction are topics of great interest in today's workplace. They provide a competitive edge in personal and professional life. However, there is scanty evidence in the Indian scenario that explores the assessment of these two notions among nurses. Therefore; this study was conducted to exhume the data regarding the assessment of Emotional intelligence and job satisfaction among nurses. The study aimed to identify the emotional intelligence and job satisfaction among nurses in selected hospitals of Udaipur. Methods: This cross-sectional study was carried out among 100 nurses at tertiary care teaching hospital from January 2021 to July 2021. Convenience sampling technique was employed for sample selection. Standardized questionnaire Schutte Self Report Emotional Intelligence Test (SSEIT) and Minnesota Satisfaction Questionnaire (MSQ) were used for data collection. Descriptive and inferential statistics (chi-square) were used for data analysis. Results: Most of the staff nurses (59%) experience high level of emotional intelligence. Emotional intelligence has found significant association with age, professional qualification, co-worker relationship and marital status and type of family. Furthermore, majority (65%) of the respondents had middle-level job satisfaction which has been found significantly associated with age, co-worker relationship, type of family, marital status and no. of children. Conclusions: Emotional intelligence and job satisfaction is an important prerequisite to becoming successful in personal and professional world. According to the study data, majority of staff nurses have higher emotional intelligence and higher job satisfaction which is directly related to an organization's production and efficiency.